Papulopustular rosacea treated with ivermectin 1% cream: remission of the Demodex mite infestation over the time and evaluation of clinical relapses - Trave, Ilaria; Micalizzi, Claudia; Cozzani, Emanuele; Gasparini, Giulia; Parodi, Aurora (Dermatology Practical & Conceptual, 2022)
Background: Topical ivermectin is an anti-inflammatory and anti-Demodex drug for papulopustular rosacea. Rosacea is a relapsing disease and the time between recurrences should be considered alongside efficacy Objectives: The aims of this study were to assess the time of first relapse and relapse rates of Demodex mite infestation and papulopustular rosacea Methods: We conducted a prospective study of subjects affected by different degrees of papulopustular rosacea. Patients that achieved a complete response after treatment were monitored every 4 weeks and up to 32 additional weeks. For each patient, we evaluated recording the time to first relapse and relapse rate of Demodex mite infestation and rosacea. Results: The overall success rate on Demodex infestation was 87.5%. only 12.5% relapse. Ivermectin leads to complete response in 70% of patients. Median time to relapse was 140 days, the mean time was 152 days. The global success rate was 54.76%. Conclusions: Topical ivermectin keeps a remission of Demodex infestation and clinical remission for long time. We proposed a twice-weekly ivermectin maintenance therapy to reduce recurrences.